2018
DOI: 10.4252/wjsc.v10.i9.119
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory role of sphingosine kinase and sphingosine-1-phosphate receptor signaling in progenitor/stem cells

Abstract: Balanced sphingolipid signaling is important for the maintenance of homeostasis. Sphingolipids were demonstrated to function as structural components, second messengers, and regulators of cell growth and survival in normal and disease-affected tissues. Particularly, sphingosine kinase 1 (SphK1) and its product sphingosine-1-phosphate (S1P) operate as mediators and facilitators of proliferation-linked signaling. Unlimited proliferation (self-renewal) within the regulated environment is a hallmark of progenitor/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 145 publications
(224 reference statements)
2
41
0
Order By: Relevance
“…A better understanding of S1P in osteoclastic/osteoblastic cells, as well as related signal pathways, is in great demand 55 . In addition to the role of S1P as a first or second messenger that regulates cell migration, differentiation, proliferation and apoptosis, we focused on osteoclast‐osteoblast crosstalk coupled with S1P 92 . Interestingly, FTY720 acts as an inhibitor of the S1P receptor and was tested in clinical experiments in 2017 93 .…”
Section: Resultsmentioning
confidence: 99%
“…A better understanding of S1P in osteoclastic/osteoblastic cells, as well as related signal pathways, is in great demand 55 . In addition to the role of S1P as a first or second messenger that regulates cell migration, differentiation, proliferation and apoptosis, we focused on osteoclast‐osteoblast crosstalk coupled with S1P 92 . Interestingly, FTY720 acts as an inhibitor of the S1P receptor and was tested in clinical experiments in 2017 93 .…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidence demonstrates that S1P is a critical second messenger that regulates the migration of various cells, not only cancer cells [25,26] but also myofibroblasts [27], dendritic cells [28] and stem cells [29]. Moreover, it has been reported that S1P generated from SphK1 accelerated breast cancer cell migration [30].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, human iPSC-EVs enhanced hepatic regeneration in hepatic ischemia-reperfusion injury rat models, by inhibiting apoptosis of hepatic cells, suppressing inflammatory responses, and attenuating the oxidative stress response [134]. Human iPSC-EVs were also reported to induce hepatocyte proliferation in vitro and in vivo in a dose-dependent manner, which is related to the activation of sphingosine kinase and sphingosine-1-phosphate signalling pathway [135], known to promote cell proliferation in various cell types [136][137][138]. Similarly, treatment with human UCMSC-EVs has been shown to ameliorate the infiltration of neutrophils and diminish oxidative stress in hepatic tissue; therefore protecting against hepatic apoptosis [139].…”
Section: Liver Regenerationmentioning
confidence: 99%